THE CORRELATION BETWEEN BODY IMAGE AND SELF ESTEEM IN ARABIC LANGUAGE EDUCATION STUDENTS CLASS 2019 AT JAMBI UNIVERSITY - Ary Myftakhul Huda; Adilia Ningtias; Elsa Arsita; Shena Nabilla; Friscilla WulanTersta (Attaqwa: Jurnal Ilmu Pendidikan Islam, 2022)
A student must have body image and self-esteem. Self-esteem can increase or decrease. This is because self-esteem is the process of evaluating a person about the experiences around them, including their body. This study aims to determine the relationship between body image and self-esteem among students of the Arabic Study Program at Jambi University in 2019. This study is a quantitative research using the type of improvement. The data collection technique in this study is a non-Test technique to measure the correction between body image and self-esteem of Arabic education students at Jambi University 2019based on research results, the result of the correction coefficient between body image and self-esteem is-0. 065 with P 0.699. Significant or p 0.05 indicates between the two variables there is no significant bond. A few categorizations have been done if in total, students of Arabic language education of the 2019 generation of Jambi University admit more to body image than self-esteem. Body image ( 65.8%) is greater than that of self-esteem (55.3%).